Efeito do plantio de Acacia mangium Willd. (Fabaceae) sobre a riqueza e diversidade arbórea em áreas de savana na Amazônia Setentrional - Sousa, Sidney Araújo de (2014)
This study aimed to estimate tree species richness and diversity in natural savannas and savannas converted to Acacia mangium plantations in northern Amazonia. All trees with base diameter greater than or equal to 2 cm were measured and identified using thin and long (250m x 2m) plots of 0.05 hectares (8 plots in savannas and 17 plots in Acacia plantations). We found 1365 individuals, 829 (60.7%) of which were of A. mangium, and the remaining 536 (39.2%) from native species. Typical savanna trees were represented by eight species (12.9%), while 34 species (54.9%) were forest species and 20 (32.2%) were habitat generalists. Most savanna species (7) were found in the understory of plantations. Only richness and diversity of forest species were positively related to plantations’ age and basal area, indicating that possibly fire exclusion and microclimatic changes are favoring the establishment of forest species in the plantation understory. The nearest distance from native forest and/or savanna patch did not explain the variation in richness and diversity of tree species found in the plantations. In conclusion, tree plantation promoted a deep change in species composition in the area, allowing the entrance of tree species not found before in local savannas. Although several savanna species were found in plantations, the results are not conclusive regarding a complementary role of forest plantations for conservation of savanna woody species in northern Amazonia. Future studies should focus on other components of biodiversity such as herbs and grasses and in determining the effects of connectivity and permeability of this landscape.